2011
DOI: 10.3174/ajnr.a2879
|View full text |Cite
|
Sign up to set email alerts
|

Patency of Branches after Coverage with Multiple Telescoping Flow-Diverter Devices: An In Vivo Study in Rabbits

Abstract: BACKGROUND AND PURPOSE:The safety of placing multiple overlapped endoluminal flow diverters remains unclear because small eloquent branch arteries theoretically could become occluded by these devices. We placed single and multiple flow diverters over small branch arteries in rabbit aortas to determine the incidence of branch artery occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…Animal studies indicate a minimal but increased incidence of branch occlusion with lower stent porosity, 20 such as what might be found after FDS implantation across the PICA ostium and with multiple overlapping stents. 21 However, our study and others did not find an association between the number of devices and branch occlusion. Animal studies indicate that the perfusion demand of tissue supplied by branch vessels that are covered by the FDS maintains branch vessel patency.…”
Section: Discussioncontrasting
confidence: 47%
“…Animal studies indicate a minimal but increased incidence of branch occlusion with lower stent porosity, 20 such as what might be found after FDS implantation across the PICA ostium and with multiple overlapping stents. 21 However, our study and others did not find an association between the number of devices and branch occlusion. Animal studies indicate that the perfusion demand of tissue supplied by branch vessels that are covered by the FDS maintains branch vessel patency.…”
Section: Discussioncontrasting
confidence: 47%
“…10,30 Importantly, small branching feeders off the parent artery appear to remain intact even when covered by telescoping flow diverters, making these diverters especially useful when treating tandem aneurysms separated by a longer distance. 4,11,14,26,30 We successfully deployed 25 PEDs to treat 38 tandem aneurysms in 17 patients. The average Raymond score at the last follow-up was 1.3, and 89% of treated aneurysms had complete occlusion at the last follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, narrowing of collateral branches is rarely reported. Preclinical studies 9,[22][23][24][25][26] reported that flow within collateral arteries was maintained after the placement of a flow diverter. However, these arteries were considered end vessels without distal collaterals.…”
Section: Side Branches and Perforators Covered By The Pedmentioning
confidence: 99%